Classification of Crucigenoid Algae: Phylogenetic Position of the Reinstated Genus Lemmermannia, Tetrastrum spp. Crucigenia tetrapedia, and C. lauterbornii (Trebouxiophyceae, Chlorophyta)1. Issue 2 (22nd February 2013) - Bock, Christina; Luo, Wei; Kusber, Wolf‐Henning; Hegewald, Eberhard; Pažoutová, Marie; Krienitz, Lothar
<x xml:space="preserve">Abstract</x> The subfamily Crucigenioideae was traditionally classified within the well‐characterized family Scenedesmaceae (Chlorophyceae). Several morpho‐logical revisions and questionable taxonomic changes hampered the correct classification of crucigenoid species resulting in a high number of synonymous genera. We used a molecular approach to determine the phylogenetic position of several Tetrastrum and Crucigenia species. The molecular results were correlated with morphological and ontogenetic characters. Phylogenetic analyses of the SSU rDNA gene resolved the position of Tetrastrum heteracanthum and T. staurogeniaeforme as a new lineage within the Oocystis clade of the Trebouxiophyceae. Crucigenia tetrapedia, T. triangulare, T. punctatum, and T. komarekii were shown to be closely related to Botryococcus (Trebouxiophyceae) and were transferred to Lemmer‐mannia. Crucigenia lauterbornii was not closely related to the other Crucigenia strains, but was recovered within the Chlorella clade of the Trebouxiophyceae.